Web-based counseling system / Kiruban Poovan - Kiruban , Poovan (2000)
There are a lot of website offering services particularly in psychology services ranging from online counseling, e-counselor, motivation to behavioral analysis. The responses from user are overwhelming for those kind of online services. However, the current web based counseling systems are mostly advertisement oriented. This is because, most of the website is playing role as a medium to advertise a particular physician business. Therefore, the scope of web based counseling system for this thesis is vary from conventional idea of web based counseling system The objective of this thesis is to produce a system that independently can identify precisely a particulars characteristic, the way he/she thinks and try to help the person to solve their problems through in depth understanding the core of their problems. But, the end system that we have produced in this thesis will only able to identify person's characteristics and their behavioral through a series of testing. Anyway, this system can be a stepping-stone for further future research to produce a pure web based counseling system. In order to complete this thesis, we have interviewed a lot of expertise in psychology and web technology as listed in reference in this report Basically, what we have done is just collection of idea of several experts. So, there should be a continuous research on this area to identify the suitable way to implement a proper web based counseling system. To conclude, the objective of this thesis has been met by producing a system that can identify a person's mentality and other counseling issues such as motivation, relaxing and observation testing.